Analysis of Machined Depth and Hole Diameter on Soda-lime Glass Using Electrochemical Discharge Machining Process - Pawar P.; Kumar A.; Ballav R. (Журнал інженерних наук)
The machining of a glass material is highly complicated due to its physical as well as chemical properties. The electrochemical discharge machining is an integrated hybrid machining process which has utilized to machining of conducting materials as well as high strength non-conducting materials having brittleness and high hardness. In this research article, the electrochemical discharge machining experimental setup was built and fabricated for machining of non-conducting materials. The electrochemical discharge machining process was applied for drilling on soda-lime glass material. The experiments were done with reference to Taguchi L27 orthogonal array approach and scrutinized by utilizing the MINITAB 17 software. The machined depth and hole diameter results were inspected after electrochemical discharge drilling on soda-lime glass material with considering the machining conditions such as voltage, electrolyte concentration, and rotation. The observation results showed that voltage is the major parameter for machined depth and hole diameter followed by electrolyte concentration and rotation of tool electrode.